Neighborhood Characteristics, Peer Networks, and Adolescent Violence - Haynie, Dana L. (Journal of quantitative criminology, 2006)
Although ecological researchers consistently find high rates of crime and violence within socioeconomically disadvantaged neighborhoods, there is little consensus as to why this pattern exists. To address this question, we use data from the National Longitudinal Study of Adolescent Health ( n =12,747) to examine three related research questions. Are neighborhood characteristics associated with adolescent violence net of compositional and selection effects? Are neighborhood characteristics associated with adolescents’ exposure to violent and prosocial peers? Does peer exposure mediate the neighborhood characteristics–violence association? Results indicate that across a wide range of neighborhoods, socioeconomic disadvantage is positively related to adolescent violence net of compositional and selection effects. Additionally, neighborhood disadvantage is associated with exposure to violent peers, and peer exposure mediates part of the neighborhood disadvantage–violence association. Joining structural and cultural explanations for violence, our findings suggest that neighborhood disadvantage influences adolescent violence indirectly by increasing opportunities for youth to become involved in violent peer networks.